2016
DOI: 10.1016/j.athoracsur.2015.12.074
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Delirium After Cardiac Surgical Procedures on Postoperative Resource Use

Abstract: Background Delirium is a common complication after cardiac surgery and is associated with increased morbidity and mortality. However, whether rigorously-assessed postoperative delirium is associated with increased length of stay in the intensive care unit (LOS-ICU), length of stay (LOS), and hospital charges is not clear. Methods Patients (n=66) undergoing coronary artery bypass and/or valve surgery were enrolled in a nested cohort study. Rigorous delirium assessments were conducted using the Confusion Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 34 publications
7
98
0
1
Order By: Relevance
“…The potential consequences of delirium after cardiac surgery have been reported in several studies (Martin et al, 2012;Saczynski et al, 2012;Otomo et al, 2013;Brown et al, 2016). In agreement with these data, our group of patients with PD had longer duration of mechanical ventilation, prolonged use of drugs such as dobutamine and norepinephrine, with more patients having acute kidney injury, tachyarrhythmia and cardiogenic shock, and the longer lengths of ICU stay.…”
Section: Post-surgical Deliriumsupporting
confidence: 90%
“…The potential consequences of delirium after cardiac surgery have been reported in several studies (Martin et al, 2012;Saczynski et al, 2012;Otomo et al, 2013;Brown et al, 2016). In agreement with these data, our group of patients with PD had longer duration of mechanical ventilation, prolonged use of drugs such as dobutamine and norepinephrine, with more patients having acute kidney injury, tachyarrhythmia and cardiogenic shock, and the longer lengths of ICU stay.…”
Section: Post-surgical Deliriumsupporting
confidence: 90%
“…In the current prospective observational study, we chose PACU-D as our primary outcome measure because of its temporal proximity to emergence and its implication as an early marker of POD. 1,52 POD (occurring on or after the first postoperative day) has revealed associations with adverse outcomes, such as increased functional decline up to 1 month after surgery, 53 cognitive decline up to 6 months after surgery, 54 length of ICU 26,55 and hospital stay, 26,55e57 hospital costs, 26,55,57,58 postdischarge institutionalisation, 26,56 30 day hospital readmission, 56 and mortality. 26,59 Our intention was to evaluate whether perioperative EEG features are associated with the development of PACU-D.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction Delirium is associated with increased mortality, reduced quality of life and increased health-care costs. 4,8,62,[194][195][196][197][198][199] As a prerequisite to estimating the cost-effectiveness of a delirium screening tool such as the 4AT, it is necessary to first characterise survival, cost and quality of life in patients with and without a diagnosis of delirium in a current UK population. The objectives of this economic evaluation within the 4AT study were to estimate the observed 12-week cumulative health-care-associated costs in these two groups of patients (delirium or no delirium) in the NHS in the three study sites.…”
Section: Chapter 6 Health Economicsmentioning
confidence: 99%